(untitled) (BIBECHANA, 2024)
Lithium ferrite (Li0.5Fe2.5O4) shows significant promise in electrical and electronic engineering. It possesses a crystal spinel crystal structure denoted as AB2O4, with "A" and "B" representing specific tetrahedral and octahedral lattice sites respectively. Analysis of X-ray diffraction (XRD) patterns aligns well with the JCPDS card (no. 38-0259), confirming the spinel structure with the Fd3m space group. However, an additional peak at 211 in the basic lithium ferrite suggests a subtle Fd3m to the P4132 phase change with a minor secondary hematite phase. Investigating the cation distribution in these ferrites is crucial for further exploration of their magnetic and dielectric properties. These ferrites find widespread applications in microwave technology and magnetic and electric energy storage devices.